2021
DOI: 10.1136/bmj.n2305
|View full text |Cite
|
Sign up to set email alerts
|

Acute urinary retention and risk of cancer: population based Danish cohort study

Abstract: Objective To examine the risk of urogenital, colorectal, and neurological cancers after a first diagnosis of acute urinary retention. Design Nationwide population based cohort study. Setting All hospitals in Denmark. Participants 75 983 patients aged 50 years or older with a first hospital admission for acute urinary retention during 1995-2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Since we excluded patients with previous prostate cancer, previously diagnosed prostate cancer could not explain the excess risk of dying from malignancies. We previously examined the association between AUR and cancer in a Danish nationwide cohort study, and found AUR to be a marker of occult urogenital, colorectal, and neurological cancer 26 . While infections can directly cause AUR, AUR hospitalization is also associated with a potential risk of nosocomial and catheter‐related infections 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since we excluded patients with previous prostate cancer, previously diagnosed prostate cancer could not explain the excess risk of dying from malignancies. We previously examined the association between AUR and cancer in a Danish nationwide cohort study, and found AUR to be a marker of occult urogenital, colorectal, and neurological cancer 26 . While infections can directly cause AUR, AUR hospitalization is also associated with a potential risk of nosocomial and catheter‐related infections 18 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously examined the association between AUR and cancer in a Danish nationwide cohort study, and found AUR to be a marker of occult urogenital, colorectal, and neurological cancer. 26 While infections can directly cause AUR, AUR hospitalization is also associated with a potential risk of nosocomial and catheter‐related infections. 18 Due to the design of our study, causation cannot be inferred.…”
Section: Discussionmentioning
confidence: 99%